2021
DOI: 10.1111/tpj.15410
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of proteins and metabolites in developing wheat grain and their differential regulatory response during the grain filling process

Abstract: SUMMARY Grain filling and grain development are essential biological processes in the plant’s life cycle, eventually contributing to the final seed yield and quality in all cereal crops. Studies of how the different wheat (Triticum aestivum L.) grain components contribute to the overall development of the seed are very scarce. We performed a proteomics and metabolomics analysis in four different developing components of the wheat grain (seed coat, embryo, endosperm, and cavity fluid) to characterize molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 104 publications
3
55
0
Order By: Relevance
“…The object of our research is the middle part of the 7 DAP spike of wheat. This is the early developmental stage, named the cellularization stage, which lasts up to 10 days [ 34 ], and is the middle of the cell division or cell expansion stage [ 35 , 36 ] or the late milk stage [ 31 ]. This stage was characterized by a high level of expression of tested TaCKX1 and TaCKX2 genes in wheat [ 27 ] and their orthologs in barley [ 37 ], and their silencing at this stage corresponded to yield-related traits [ 7 , 8 , 15 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The object of our research is the middle part of the 7 DAP spike of wheat. This is the early developmental stage, named the cellularization stage, which lasts up to 10 days [ 34 ], and is the middle of the cell division or cell expansion stage [ 35 , 36 ] or the late milk stage [ 31 ]. This stage was characterized by a high level of expression of tested TaCKX1 and TaCKX2 genes in wheat [ 27 ] and their orthologs in barley [ 37 ], and their silencing at this stage corresponded to yield-related traits [ 7 , 8 , 15 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using transcriptomics and iTRAQ-labelling proteomics to probe the early stages of wheat grain development, Yang and colleagues quantified and identified 85,000 genes and 7500 proteins [ 7 ]. Zhang and colleagues used deep proteome and metabolome analyses to shed light on the wheat grain filling process, where they dissected grains into seed coat, embryo, endosperm, and cavity fluid during major developmental stages to reveal the dynamic accumulation patterns of molecules over space and time [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most popular LC systems in proteomics apply reverse phase (RP) conditions which separate molecules based on their hydrophobicity and retention time (RT). RPLC–MS not only helps separate compounds bearing identical m / z that cannot be differentiated by MS alone, but also allows for the detection of low-abundance molecules by separating them from higher abundance ones [ 8 ]. Shotgun bottom-up or peptide-centric proteomics is the most common gel-free approach in which whole protein samples are digested into peptides prior to LC–MS/MS analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The proteomics study of rice grains during development found that proteins involved in glycolysis and TCA cycle accumulated at a high level at the end of grain maturity (Lee and Koh, 2011). In wheat seeds, glycolysis and starch synthesis was significantly enhanced at the late stage of grain filling, which provided much energy for grain maturity (Zhang N. et al, 2015;Zhang et al, 2021). In this study, 16 DEPs in lotus embryo involved in the glycolysis pathway, of which 7 proteins (fructokinase, pyruvate decarboxylase, fructose-bisphosphate aldolase, etc.)…”
Section: Carbohydrate and Energy Metabolism During Lotus Seed Dehydration And Maturitymentioning
confidence: 99%